The Circulation Distribution on the Lifting Line for a Given Extracted Power - Ali Helali; Badreddine Kamoun; David Afungchui; Mohamed Jomaa Safi (International Journal of Rotating Machinery)
Presently, there exist few numerical methods which treat the inverse problem for the determination of the geometry of wind turbine blades. In this work, authors intend to solve the inverse optimum project for horizontal axis wind turbine in which the selection of the circulation distribution is obtained by resolving two variational problems: the first consists in sorting the circulation distribution on the lifting line, which, for a given power extracted by the wind turbine, minimizes the loses due to the induced velocity. In the second, the optimal circulation distribution is selected such that the kinetic energy of the wind downstream of the rotor disc is minimum, when the energy extracted by the wind turbine for one rotating period is imposed. A code has been developed which incorporates the real pitch of the helicoidal vortex wake. Very promising results have been obtained: the circulation distribution for a given extracted power and the chord lengths distribution law along the blade span.